PENGARUH LITERASI DIGITAL TERHADAP KESADARAN WARGA BELAJAR PKBM DALAM PEMANFAATAN TEKNOLOGI DIGITAL - Firdaus, Nunu Mahmud; Wahyudin, Uyu; Sudiapermana, Elih; Shantini, Yanti (Comm-Edu (Community Education Journal), 2025)
The rapid development of digital technology that occurs requires human society to start updating and improving their skills. The users of digital media must be able to develop an evaluative disposition towards digital content. Without critical evaluation, users will be more easily carried away by the flow of technology than controlling it. Therefore, this study seeks to reveal the influence of digital literacy on the digital awareness of PKBM learners. The subjects in this study were determined purposively by determining a quota sample. This study was designed in the form of a mix method with data collection applying observation techniques and questionnaires distribution. The analysis was carried out using interactive model analysis techniques for qualitative data and regression analysis for quantitative data. The results of this study indicate that the mastery of digital literacy by PKBM learners is quite high. Likewise, the digital awareness of learners is generally categorized as good. This is evidenced by the results of the correlation-regression analysis which shows a significant positive influence.